2013
DOI: 10.15580/gjas.2013.3.032713547
|View full text |Cite
|
Sign up to set email alerts
|

Mycoflora of Three Fish Species Smoke-Dried Using Rubber Wood (Hevea Brassillensis) in Nigeria

Abstract: A study of the mycoflora of three fish species: Lutjanus agennes (Red Snapper), Mugil cephalus (Mullet), Chrysichthys walkeri (Catfish) smoke-dried using Rubber wood (Hevea brassillensis) was carried out. Fish samples were bought from Ogbe-Ijoh market in Warri, Delta State and smoked using a traditional rectangular mud kiln (Chorkor) and stored on open benches in the laboratory at room temperature. Samples from the smoke-dried fish species were assessed tri-weekly using amended potato dextrose agar during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…They also observed a significant (p < 0.05) increase in the percentage of total protein, lipid and ash contents with increased storage time while percentage crude fat and moisture content decreased significantly (p < 0.05) with increased storage time. Akise et al (2013) reported an increase in the moisture content and fungi count of smoked Lutjanus agennes (Red Snapper), Mugil cephalus (Mullet), Chrysichthys walker during storage at room temperature for 6 weeks. Ihuahi et al (2010) found Clarias angullaris to be in acceptable conditions for 12 days of icestorage in insulated ice box.…”
Section: Determination Of Fish Spoilagementioning
confidence: 99%
“…They also observed a significant (p < 0.05) increase in the percentage of total protein, lipid and ash contents with increased storage time while percentage crude fat and moisture content decreased significantly (p < 0.05) with increased storage time. Akise et al (2013) reported an increase in the moisture content and fungi count of smoked Lutjanus agennes (Red Snapper), Mugil cephalus (Mullet), Chrysichthys walker during storage at room temperature for 6 weeks. Ihuahi et al (2010) found Clarias angullaris to be in acceptable conditions for 12 days of icestorage in insulated ice box.…”
Section: Determination Of Fish Spoilagementioning
confidence: 99%
“…Otherwise, it will become unfit for ingestion by humans, and even after being treated, the fish may continue to be spoiled, especially if traditional procedures were applied (Oparaku and Mgbenka 2012, Shewan 2000). The tech-nique of preserving food like fish involves several processes that prevent the growth of microorganisms such as the addition of growthinhibiting substances or customized storage conditions by freezing or drying (Akise et al 2013). For thousands of years, smoking has been applied to prepare and preserve food (Krasemann, 2004) In seafood, some fungal species are capable of producing mycotoxins as aflatoxins (AFs), Fusarium mycotoxins, and ochratoxins (OTs) (Nourbakhsh and Tajbakhsh 2021and Shamimuzzaman et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Fish is a very important source of animal protein in the diets of man. They constitute about 60% of the total protein intake in adults especially in the rural areas (Akise et al, 2013). In Nigeria, fish is eaten fresh, preserved or processed (smoked) and form a much-cherished delicacy that cuts across socioeconomic, age, religious and educational barriers (Adebayo-Tayo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%